Students Perception of Culturally Relevant Pedagogy in English Language Learning in East Kalimantan - Nurfani Yulianti; Abdul Halim; Ibrahim (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research explores students’ perceptions of culturally relevant pedagogy (CRP) in English language learning to identify its benefits and challenges. CRP emphasizes integrating students’ cultural identities into the learning process to enhance understanding and engagement. This qualitative study involved 30 students from three different classes, with data collected through individual interviews and student reflection questionnaires, then analyzed using thematic analysis. The findings show that students generally have a positive view of CRP; they find it easier to understand the material and feel more motivated and emotionally connected when culture is involved. The main advantages are the relevance of the material to students’ lives and the use of cultural media such as movies and music. However, two key challenges emerge: cultural disconnect and limitations of traditional teaching methods that fail to address students’ diverse backgrounds. These results highlight the need for in-depth teacher training and the development of an inclusive, culturally informed curriculum to maximize the benefits of CRP in English language learning. The findings can guide teachers and curriculum developers to design lessons and materials that better reflect students’ cultural backgrounds and learning needs.